Gene expression, phylogenetic and syntenic analyses of pantophysin (Pan I) and synaptophysin-like2 (Sypl2) genes in Atlantic cod (Gadus morhua L.) - Stjelja, Suzana (2012)
The pantophysin (Pan I) locus reveals differences between Norwegian coastal cod (NCC) and Northeast Arctic cod (NEAC) populations that are highly significant, temporally stable and larger than for any other genetic marker. However, the biochemical basis for the selection and the functional role of pantophysin in fishes are unknown. The observed polymorphism might be related to different expression and/or function of the different Pan I genotypes. We applied several different approaches to investigate evolutionary history and spatio-temporal expression patterns of Pan I and synaptophysin-like2 (Sypl2) gene in Atlantic cod. ln silico analyses identified pantophysin, synaptophysin and synaptophysin-like genes in various vertebrates, including Atlantic cod. Multiple alignment of amino acid sequences in Atlantic cod and other teleosts revealed a conserved structure characterized by the MARVEL domain, indicating functionally important parts of the examined proteins. Phylogenetic analysis showed that a number of examined vertebrates classified into clade of teleosts and tetrapods. In the teleost clade, separated from tetrapods two clusters were formed. Various taxa from the class Actinopterygii with Pan I clustered together with Sypl1b and Sypl2b, while Sypl1 and Sypl2 clustered together with Sypl1a and Sypl2a. Teleosts with Sypl1 sequences clustered together and formed a separate clade. Similar, tetrapods with Sypl1 clustered together, except Xenopus Sypl1 that formed a separate branch. The tetrapods Sypl2 also cluster together, forming a separate clade. The teleosts Syp clustered together with tetrapod orthologs, indicating a common origin. Regions closely linked to Atlantic cod Pan I, Sypl2 and Syp1 and ortologhous genes in medaka, zebrafish, Xenopus and human displayed well conserved synteny. The constructed phylogenetic tree and syntenic analysis revealed incorrect sequence naming in several species, including cod Pan I. Since pantophysin expression in fish has not yet been investigated, this study provides the first characterization of the Pan I and Sypl2 spatio-temporal expression patterns in Atlantic cod. Using quantitative PCR analysis expression of Pan I and Sypl2 was quantified in early life stages in NEAC. Both genes were expressed from late gastrula with 8 somites until the larval size of 10-15 mm body length, indicating functional significance during early cod development. The Sypl2 transcript was identified by whole mount in situ hybridization (WISH) in the embryonic head, heart and liver. In the cod larvae Sypl2 mRNA was detected in the eye, liver, heart, neuromast, ceratohyal and ceratobranchial arches, mandible and pectoral fin. Ubiquitous expression of Pan I and Sypl2 was revealed in various tissues in adult NEAC and NCC. The highest Pan I mRNA levels were detected in the head kidney, spleen, epithelial mucus and ovaries while the muscle, testicles and epithelial mucus exhibited the highest Sypl2 expression. Interestingly, an inverse expression pattern between Pan I and Sypl2 was observed in the muscle, head kidney and spleen in examined NEAC, while in NCC both genes showed similar expression patterns with the highest gonadal and epithelial expression.